THE USE OF SKYPE IN TEACHING LISTENING COMPREHENSION - Rugaiyah Rugaiyah (Universitas Negeri Padang, 2015)
This paper shows the ELT educational trend has recently been gaining in significance in education systems throughout the word. English Language Teaching (ELT) has tremendously changed over the last one decade. Living in a world where technology is omnipresent. Technology in education has become the buzz word in every educational environment. The classroom environment today, is completely different from the traditional classroom. The traditional methods which are mainly based on lecturing and rote learning. Whereas, technologies like internet, skype, youtube, tweeter, Mobile phones and many more have added not only stimulus but also learners' engagement and true interactivity with the classroom. The internet has had a tremendous impact on learning and brought new opportunities for learners to find and retrieve information, access learning resources, as well as to connect with other learners. Internet appeared to be entering a new phase of development with a nerver range of applications, tools and services. Teachers and learners are able to use technological tools such as: quizzes to test knowledge: search tools to retrieve information online, as well as discussion boards. email, and life chart, which facilitated communication. These tools certainly has the potential to enhance the learning process by offering more flexible access to the curriculum and providing opportunities for support outside the classroom. One widespread method online teaching involves the use of skype, a powerful application that provides users with free internet voice chatting service. This paper is focused on analyzing the impact of Skype on students' listening comprehension for a group of 21 students of fourth semester of FKIP UIR Pekanbaru in academic year 2014/2015. This study used classroom action research. The researcher collaborated with one of the English lecturer who teaches at English language of FKIP UIR. The instruments of this research were tests, observation, interview, and field notes. The data collection nas accomplished by means of students' reflection questionnaires posterior to the Skype, field notes of the inlestigator, and comprehension tests. The finding shorws that the use of Skype can improve students' listening comprehension. It can be seen from the increasing of mean score of the tests, includes:base score has 46.19, cycle I was 69.52, and cycle II was 71.43.